Determinants of Commercial Bank Performance with Guarantee Interest as Moderating Variables in Banks Listed on IDX 2016 – 2020 - Dhanang Hartanto; Andam Dewi Syarif (Syntax Corporation Indonesia, 2022)
This study aims to analyze and examine the effect of the Efficiency Ratio (BOPO), Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Non-Performing Loan (NPL), Size (SIZE) with LPS Guarantee Interest Rate (SBP) as a moderating variable on the Return On Assets (ROA) of Commercial Banks listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling method used is purposive sampling, including the observation of 38 commercial banks listed on the Indonesia Stock Exchange from 2016 to 2020. The statistical analysis method used is a descriptive quantitative method with the type of data being time series and cross-section using moderated regression analysis method (MRA). The results showed that the determinants of Operating Costs with Operating Income (BOPO) and Guarantee Interest Rate (SBP) had a positive and significant effect on Return On Assets (ROA), Non Performing Loans (NPL) had a significant negative effect on Return On Assets (ROA). The Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Bank Size (SIZE) do not affect Return On Assets (ROA). The results of the Moderating Guarantee Interest Rate (SBP) moderate the effect of Operating Costs with Operating Income (BOPO) and moderate the effect of Non-Performing Loans (NPL) on Return On Assets (ROA). It is believed that the Guaranteed Interest Rate (SBP) has force power as a determinant of the level of profitability or performance of the bank, either directly or indirectly.